Web services concepts, methodologies, tools, and applications (Engineering Science Reference, an imprint of IGI Global, 2019)
"This book is an innovative reference source that examines relevant theoretical frameworks, current practice guidelines, industry standards, and the latest empirical research findings in web services. Highlighting a range of topics such as cloud computing, quality of service, and semantic web"--